Penanganan Kegawatdaruratan Akibat Sengatan Hewan Laut Berbisa: Pengalaman Nelayan (Pajeko) Di Desa Gamhoku - Olivia Asih Blandina; Roberto Cabu; Yasmin Tatuwo (Universitas Sumatera Barat, 2026)
Emergency situations do not only occur due to very heavy road traffic, but also within the family and residential areas often occur. This study aims to determine the Analysis of Emergency Handling Due to Venomous Marine Animal Stings: Fishermen's Experience (pajeko) in Gamhoku Village. This study uses a qualitative method. The results of the study stated that there are several influencing factors, namely Understanding of Emergency: for fishermen, handling stings does not only include formal medical measures, but also often includes traditional medicine, local beliefs, and empirical experience. Types of Venomous Marine Animals Encountered: Respondents mentioned jellyfish, stingrays, and sea pig spines as venomous marine animals that are often encountered. First aid: Most fishermen do not have a correct understanding of first aid protocols. The role of training and availability of tools stated that they had attended training, but had never received first aid equipment. Access to healthcare: All respondents stated that treatment at healthcare facilities such as community health centers (Puskesmas) or regional hospitals (RSUD) resulted in faster recovery, generally within about a week. Furthermore, challenges and risks at sea: All respondents expressed concern about stings occurring far from land, especially during storms and extreme weather.